Perversão Sexual (Sofia, 2025)
NAGEL, Thomas. Sexual Perversion. The Journal of Philosophy, New York, v. 66, n. 1, p. 5–17, 16 jan. 1969. Disponível em: http://www.jstor.org/stable/2024152. Acesso em: 13 mai. 2025.